Evaluasi Jumlah Operator pada Bagian Refinery dan Fraksinasi Plant 3-4 di PT SMART Tbk. Surabaya - Kornelius Kornelius; Nova Sepadyati (Jurnal Titra, 2019)
PT. SMART Tbk. is a company engaged in processing palm oil which was established in 1962. PT SMART Tbk. Always keep informed of technological developments in terms of updating the machines used to process their palm oil. Because their machines running almost entirely automatic, PT SMART Tbk. want to know the number of operators or field workers that are appropriate. The method used is the full time equivalent method with the help of the work sampling method in observation to get its productivity. The purpose of this study is to propose the number of operators based on the full time equivalent index. The results of this study are the reduction of refinery 4 operators by 1 person per team or 3 people as a whole and a comprehensive proposal that gives a reduction of 4 people per team or 12 people as a whole. The proposal is projected to be able to provide annual profits of 139-557 million rupiah depending on which proposals are carried out by the company.